Observer-Based Control for Nonlinear Time-Delayed Asynchronously Switching Systems: A New LMI Approach - Amin Taghieh; Ardashir Mohammadzadeh; Jafar Tavoosi; Saleh Mobayen; Thaned Rojsiraphisal; Jihad H. Asad; Anton Zhilenkov (Mathematics, 2021)
This paper designs an observer-based controller for switched systems (SSs) with nonlinear dynamics, exogenous disturbances, parametric uncertainties, and time-delay. Based on the multiple Lyapunov–Krasovskii and average dwell time (DT) approaches, some conditions are presented to ensure the robustness and investigate the effect of time-delay, uncertainties, and lag issues between switching times. The control parameters are determined through solving the established linear matrix inequalities (LMIs) under asynchronous switching. A novel LMI-based conditions are suggested to guarantee the <semantics>H∞</semantics> performance. Finally, the accuracy of the designed observer-based controller is examined by simulations on practical case-study plants.